AGRICULTURAL BIOTECHNOLOGY AND ETHICAL ISSUES - Ashwini A (African Journal of Environmental Economics and Management, 2025)
Moral or ethical values are deeply held beliefs about what is right and wrong. Ethical issues arise when these values conflict with one another over an action, policy, or technology. Ethical issues can be personal. I can have a conflict about whether I should repay a debt to a friend when I know that he will use the money to feed his gambling addiction. Ethical issues associated with agricultural biotechnology, however, are social, people have beliefs about biotechnology that conflict with those of others. Environmental and food safety issues arise because some people think that biotechnology is ethically right, while others think it is wrong. These views are based on different predictions of the impacts of biotechnology. There are other similar issues in this regard. For example, what will be the impacts on peasant farmers in poor countries? How will biotechnology affect global trade? In time, these issues may disappear as we become more experienced with biotechnology and as scientists become better able to assure opponents that biotechnology provides benefits without any significant risks.